Rhetoric: How Politicians Manipulate Language and the Media to Shape Public Thought (Hinckley Journal of Politics; Vol 8 (2007), 2017)
This essay analyzes how politicians use the art of political rhetoric and framing to alter public opinion and the mediaâ€˜s receptiveness to the rhetoric. By analyzing the way politicians have used the terms â€œglobal climate change,â€ â€œtax relief,â€ â€œthe war on terror,â€ â€œtheory,â€ â€œtorture vs. abuse,â€ and the language framing abortion and controversial George W. Bush administration policies, the essay shows how politicians can use the power of words to gain political support from the public. The analysis then turns to the mediaâ€™s failure to act as a middle ground for the public. The essay examines how the media, due to the influence of money, does not offer an unbiased opinion. Finally, the essay explores the mediaâ€™s failure to act as an extra-constitutional â€œcheck and balanceâ€ to governmentâ€™s power.